"Educational History, the Spatial Turn, and Digital Scholarship: Reflections on the concept of educational spaces" - Gaffield, Chad (Université d'Ottawa | University of Ottawa, 2016)
At the heart of the discipline of History is a conviction that context matters. But there seems to be less and less agreement on how to define the appropriate context for research. National history is having a particularly hard time these days as researchers focus on the changing flows of ideas and people, processes and products, across official geo-political boundaries. But micro history is similarly in trouble for having distracted researchers from the suppos- edly important historical questions or for becoming trivial in comparison to Big History (Guldi/Armitage 2014). At first glance, such developments may appear to complicate rather than clarify metaphysical and epistemological decisions especially for educational historians who have so successfully shown the central importance of mass schooling to the making of modernity. Indeed, such research during the past half-century has played an important role in the re-thinking of the nineteenth and twentieth centuries. Micro histories compellingly analyzed school at- tendance patterns in the context of changing family and community life. National histories revealed how governments embraced schools as projects of state formation. Thematic studies showed how education reflected and inspired changing norms, policies and experiences of class, gender and ethnicity. Taken together, such work along with many other contributions moved educational history from the margins to the mainstream of efforts to understand the profound transformations following the Age of Revolutions.
Keywords: Education; History; Spatial Analysis; Digital Humanities